Zustand und Entwicklung ausgewählter Fischbestände - Einschätzung des ICES im Herbst 2002 - Zimmermann, Christopher; Hammer, Cornelius (2002)
During the autumn session of the ICES Advisory Committee for Fisheries Management (ACFM) 58 stocks assessed in six Working Groups have been analysed and reviewed, among these the demersal stocks in the North Sea and the Mackerel stock in the North East Atlantic. As in previous years, ICES recommends a reduction in fishing mortality for a number of stocks or even the establishment of recovery and management plans, to safeguard a continuous development of the stocks towards safe biological limits. ICES recommended the closure of the directed cod fishery and any fishery taking cod as by-catch in the North Sea, west of Scotland and in the Irish Sea. This will have a significant impact on the mixed round fish fisheries targeting haddock and whiting. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery Research in 2010.